WHY INDEPENDENCE IS SARAWAK'S BEST OPTION STRATEGIES TO DEVELOP SARAWAK INDEPENDENTLY OF THE FEDERAL GOVERNMENT - Wong, Philip Pak Ming (Philip Wong Pak Ming, 2023)
A land as vast and rich in resources as Sarawak should not be lacking in terms of development compared to other Asean neighbours, the current under-developed status is directly the result of bad poliies and lack of vision for Sarawak to be as successful as other countries in many achievements. Philip Wong shares his vision of how Sarawak could be developed in practical and socially acceptable ways for the land where he was born in.